Institutional and fieldimpediments facing female reporter whilecoveringsporting events - djouadi, safaa (sports creativity, 2025)
This study aims to know and identify the most important obstacles facing the female reporter on "beur tv" channel, within institutional and outside the studio fields. and also, to know the reasons that hinder the transmission of information about sports events from the point of view of sports female reporters, working in the channel’s sports section(service). The study was conducted on all female reporters working in (beur tv), whose number is estimated at (14). A questionnaire has been designed for those reporters, which included the various aspects of hinders inside and outside the establishment. The following are the main results of the survey: - Multiple professional problems while performing tasks inside and outside the channel institution. By outside, I mean in the sports ground or any other outings, including the problems of obtaining information about sports events. - There are many other handicaps that prevents the professional experience for these enthusiastic journalists , notably Institutional and field impediments. - Inequality in dealing with them; in addition to the multiplicity of occupational restrictions such as: Difficulty conducting personal interviews with officials in sports federations, heads of clubs, annoyances, harassments, low-wages, no incentives,